Missionary diplomacy religion and nineteenth-century American foreign relations - Conroy-Krutz, Emily (Ithaca London Cornell University Press, 2024)
"Missionary Diplomacy traces the connections between the Protestant foreign mission movement and the US State Department over the nineteenth century, with particular attention paid to the development of new ideas about citizenship, religious freedom, and humanitarianism."--
A missionary-diplomatic family -- Politicians -- Experts -- Citizens -- Consuls -- Victims -- Troublemakers -- Workers -- Imperialists -- Boxers -- Witnesses -- Humanitarians -- Washington DC, 1924.
Literaturverzeichnis: Seite 313-329. - Index
Keywords: Christianity and international relations -- United States -- History -- 19th century; Missionaries -- Political activity -- History -- 19th century; Protestantism -- Influence; United States -- Foreign relations